2020
DOI: 10.1039/c9ra10280a
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive polymeric nanoparticles with tunable sizes for targeted drug delivery

Abstract: Novel nanoparticles for efficient drug delivery were designed and constructed using polymeric 2,3-dialdehyde cellulose (DAC). The drug DOX was encapsulated into nanoparticles and underwent thoroughly controlled release in acidic tumor microenvironments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 48 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Doxorubicin was encapsulated in this system and showed higher stability in the alkaline and neutral medium and also observed controlled release behavior of an antitumor agent. [132] The journey of nanocarriers starts from Doxil, the clinically approved liposomal doxorubicin and liposomal drug delivery system is more advantageous than others due to its safety and effectiveness. [133,134] The systems under clinical trial include Dauno Xaume, Mayocet, Marqibo, Mepact, Abelcet, Amphotec, DepoDur, Exparal, EpaXal, Inflexal, etc.…”
Section: Recent Reports On Therapeutic Applications Of Drug Delivery ...mentioning
confidence: 99%
“…Doxorubicin was encapsulated in this system and showed higher stability in the alkaline and neutral medium and also observed controlled release behavior of an antitumor agent. [132] The journey of nanocarriers starts from Doxil, the clinically approved liposomal doxorubicin and liposomal drug delivery system is more advantageous than others due to its safety and effectiveness. [133,134] The systems under clinical trial include Dauno Xaume, Mayocet, Marqibo, Mepact, Abelcet, Amphotec, DepoDur, Exparal, EpaXal, Inflexal, etc.…”
Section: Recent Reports On Therapeutic Applications Of Drug Delivery ...mentioning
confidence: 99%
“…Another issue that plagues the reputation of nanoparticle-administered drug delivery is the biocompatibility of the nanoparticles. In research, the in vitro evaluation of the nanoparticle’s cytotoxicity to A549 cells was conducted with the help of CCK-8 analysis . It was concluded that since the derivatives of cellulose are nontoxic, biocompatible, stable, and hydrophilic, the NPs did not show any toxicity toward A549 cells (Figure b).…”
Section: Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…(c) Viability of the cells was plotted against the different dosages of DOX. Reproduced with permission from ref . Copyright 2020 The Royal Society of Chemistry.…”
Section: Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…These agents are mainly categorized as organic or inorganic nanocarriers and brought tremendous achievement in treating various infectious diseases. These organic nanometric agents include different polymeric agents ( Begines et al, 2020 ; Kong et al, 2020 ; Palanikumar et al, 2020 ; Siddiqui et al, 2020 ), lipid-based carriers ( Barkat et al, 2020 ; Plaza-Oliver et al, 2021 ), dendrimers ( Mandal, 2021 ; Nikzamir et al, 2021 ) and micelles ( Atanase, 2021 ; Hwang et al, 2020 ). These agents are widely employed for the treatment of various dreadful diseases.…”
Section: Introductionmentioning
confidence: 99%